(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Phenytoin, a widely used antiepileptic drug, in a loading dose of 15–20 mg/kg, followed by a maintenance dose of 4–7 mg/kg/day in divided doses, can lead to toxicity if the dose is exceeded, causing adverse neurological and systemic effects. This case report provides a concise overview of phenytoin toxicity, encompassing its mechanisms, clinical manifestations, and management. Common symptoms include ataxia, nystagmus, and altered mental status, while severe cases may involve cardiovascular and hematological complications. Monitoring serum levels, prompt recognition, and appropriate dose adjustments are crucial in preventing toxicity. Clinicians must maintain a high index of suspicion, as early intervention significantly impacts patient outcomes. This case report underscores the importance of vigilance and tailored interventions to mitigate the risks associated with phenytoin toxicity.